2020
DOI: 10.31219/osf.io/4wbd8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Proposed Framework Based On Literature Review of Online Contextual Mental Health Services to Enhance Wellbeing and Address Psychopathology During COVID-19

Abstract: Coronavirus disease (COVID-19) became a pandemic and is causing unprecedented biopsychosocial, spiritual and economic issues across the world while mostly affecting unprivileged populations. Turkey has gradually implemented new regulations, which slowly affected the entire country and increased the need for mental health services disproportionally. We conducted a comprehensive literature review on mental health in Turkey during COVID-19. There was no well-grounded peer-reviewed manuscripts or projects utilized… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 42 publications
0
32
0
2
Order By: Relevance
“…problem focused-coping, avoidance, seeking social support, and positive appraisal of the situation) to deal with negative psychological outcomes resulted from outbreaks such as fear, anxiety, depression, post-traumatic stress disorders, anger, grief and loss, guilt, and stigmatization. Furthermore, Tanhan ( 2020 ) suggests that utilizing an online photovoice approach can be an effective way to deal with biopsychosocial spiritual and economic issues during the COVID-19 pandemic. He argued that such a method can contribute to empowering people and communities to improve their well-being and address biopsychosocial, spiritual, and economic issues via advocacy and collaboration with people, communities, and key individuals and institutions.…”
Section: Mediating Effect Of Copingmentioning
confidence: 99%
See 2 more Smart Citations
“…problem focused-coping, avoidance, seeking social support, and positive appraisal of the situation) to deal with negative psychological outcomes resulted from outbreaks such as fear, anxiety, depression, post-traumatic stress disorders, anger, grief and loss, guilt, and stigmatization. Furthermore, Tanhan ( 2020 ) suggests that utilizing an online photovoice approach can be an effective way to deal with biopsychosocial spiritual and economic issues during the COVID-19 pandemic. He argued that such a method can contribute to empowering people and communities to improve their well-being and address biopsychosocial, spiritual, and economic issues via advocacy and collaboration with people, communities, and key individuals and institutions.…”
Section: Mediating Effect Of Copingmentioning
confidence: 99%
“…People who are under the high risk of infection, stress, and burnout can develop common mental health problems such as anxiety, depression, and fear (Bao et al 2020 ; Tanhan 2020 ). For example, studies related to COVID-19 conducted in Turkey reported high levels of anxiety, stress, depression and burnout (Yildirim et al 2020 ; Tanhan et al 2020 ; Yıldırım and Solmaz 2020 ), and death distress (Yıldırım and Güler 2020 ). There have also been various studies that have investigated the prevalence of psychological distress among different populations during the pandemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is evidence that COVID-19 may exacerbate certain cardiovascular symptoms and lead to cardiovascular complications [ 13 ]. Finally, some mental disorders have even been aggravated during this pandemic [ 14 ]. In this sense, nurses are central to COVID-19 prevention and the care of infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 outbreak initially started in December 2019 in China and spread rapidly to other countries by affecting almost all aspects of human life such as health, social, education, and economy (Tanhan 2020 ; Tanhan et al 2020 ). According to daily statistics published by the Johns Hopkins University, as of 2 October 2020, there have been more than 34 million people confirmed with COVID-19 globally and more than 1 million deaths touching 188 countries and territories (Center for Systems Science and Engineering 2020 ).…”
mentioning
confidence: 99%